PREFERENSI KONSUMEN TERHADAP BUAH-BUAHAN DI KOTA BANDAR LAMPUNG - Riski Tuan Abda’u; Bustanul Arifin; Muhammad Ibnu (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
Fruit consumption in Indonesia, especially in Lampung Province, has not reached the Nutrient Adequacy Ratio (NAR) yet, and this threatens the health of young people in the future.  Efforts to improve the consumption begin by analyzing the influence of social and personal factors then evaluate consumer preferences for fruits in Bandar Lampung.  The consumer preferences explained by different attributes combination for several fruits, such as mangoes, oranges, and bananas.  Data were collected with the survey method to 100 respondents.  Social factors significantly influence fruit consumption.  The social factors relate to the influence of other peoples that affects fruits consumptions.  Price is an essential attribute considered by consumers when choosing fruits.  Consumers prefer cheap fruits, sweet tasted, small, and clean skinned. Key words: conjoint analysis, consumption, fruit, preferences